Dependence of the Raman spectrum characteristics on the number of layers and stacking orientation in few‐layer graphene. Issue 11 (15th July 2015) - Bayle, Maxime; Reckinger, Nicolas; Huntzinger, Jean‐Roch; Felten, Alexandre; Bakaraki, Ahmad; Landois, Périne; Colomer, Jean‐François; Henrard, Luc; Zahab, Ahmed‐Azmi; Sauvajol, Jean‐Louis; Paillet, Matthieu
Abstract : Few‐layer graphene (FLG) samples prepared by two methods (chemical vapor deposition (CVD) followed by transfer onto SiO2 /Si substrate and mechanical exfoliation) are characterized by combined optical contrast and micro‐Raman mapping experiments. We examine the behavior of the integrated intensity ratio of the 2D and G bands ( A 2D / A G ) and of the 2D band width ( Γ 2D ) as a function of the number of layers ( N ). For our mechanically exfoliated FLG, A 2D / A G decreases and Γ 2D increases with N as expected for commensurately stacked FLG. For CVD FLG, both similar and opposite behaviors are observed and are ascribed to different stacking orders. For small (respectively, large) relative rotation angle between consecutive layers ( θ ), the values of the A 2D / A G ratio is smaller (respectively, larger) and the 2D band is broader (respectively, narrower) than for single‐layer graphene. Moreover, the A 2D / A G ratio decreases (respectively, increases) and, conversely, Γ 2D increases (respectively, decreases) as a function of N for small (respectively, large) θ . An intermediate behavior has also been found and is interpreted as the presence of both small and large θ within the studied area. These results confirm that neither A 2D / A G nor Γ 2D are definitive criteria to identify single‐layer graphene, or to count N in FLG. Abstract : Combining simultaneous Raman spectroscopy and laser optical contrast mapping, Bayle et al. discuss the evolution of the Raman features in few‐layer graphene for which the number of layers is independently determined by optical contrast. The authors examine mainly the dependencies of the 2D band width and the 2D‐over‐G integrated intensity ratio as a function of the number of layers since these parameters have been used as metrics to distinguish graphene and multilayer graphene.